2017
DOI: 10.1111/cen.13334
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective evaluation of a week one overnight metyrapone test with subsequent dynamic assessments of hypothalamic‐pituitary‐adrenal axis function after pituitary surgery

Abstract: Overnight metyrapone test within the first week after pituitary surgery was no better than an early morning cortisol level at predicting glucocorticoid requirement at 6 months. OMT at week 6 demonstrated recovery of HPA axis in a substantial proportion of participants who failed earlier assessments; thus, definitive testing should be delayed until 6 weeks post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We acknowledge that one or two cases of adrenal insufficiency may have been missed using this approach. We used standard HPA axis stimulation tests in routine clinical use in our department, which have been recently compared with the ITT and validated in the setting of pituitary surgery (36). While the insulin tolerance test is considered the gold standard, this would not be the test that the average practising clinician would order for a patient on opioids, and we wanted the study to have clinical relevance.…”
Section: :6 359 Clinical Studymentioning
confidence: 99%
“…We acknowledge that one or two cases of adrenal insufficiency may have been missed using this approach. We used standard HPA axis stimulation tests in routine clinical use in our department, which have been recently compared with the ITT and validated in the setting of pituitary surgery (36). While the insulin tolerance test is considered the gold standard, this would not be the test that the average practising clinician would order for a patient on opioids, and we wanted the study to have clinical relevance.…”
Section: :6 359 Clinical Studymentioning
confidence: 99%
“…In Volume 87, Issue 1 (July 2017) of Clinical Endocrinology , the co‐authors Emma L. Duncan and Ross Cuneo should be acknowledged as joint Senior Authors. The authors regret this error …”
mentioning
confidence: 98%
“…De Vries et al reported a cortisol cut-off value of 325 nmol/L with 100% sensitivity [6] (compared to ITT after a mean of 8 months), measured on an electrochemiluminescent immunoassay (Roche cobas 8000 module e602). English et al reported an optimal cut-off value of 320 nmol/L (determined on a Beckman DxI800 immunoassay analyser) with a sensitivity of 84% (CI 60-97) (cortisol measured on POD3 or POD4, compared to glucocorticoid requirement after 6 months) [8]. Application of a cut-off of 325 nmol/L in our study would result in 5 patients with adrenal insufficiency that would have been missed (leading to a sensitivity of 78%).…”
Section: Discussionmentioning
confidence: 67%
“…The metyrapone test has been established as a safe and reliable test to determine adrenal insufficiency [8]. In our pituitary center there is long-term experience with this test which was internally validated within our center [9].…”
Section: Introductionmentioning
confidence: 99%